ArtApki w edukacji plastycznej uczniów w wieku wczesnoszkolnym - Dorota Sobierańska (Problemy Wczesnej Edukacji)
An important problem of the present is the preparation of young people to live among an increasing number of visual messages that come from the world of traditional and modern art and among visual messages from the media environment. In this situation, it is necessary to change early school art education from the traditional transfer of knowledge into educational settings through which students actively develop visual literacy. The artistic applications presented in the text, available on the websites of American museums, are one of the means leading to this goal. However, it should be emphasized that these applications should be a supplement rather than an alternative to school activities, and their selection and use must be carefully thought over.